A Contribution to the UV Dose Concept for Bacteria Disinfection in Well Mixed Photoreactors - Labas, Marisol Daniela (2006)
A modified dose concept for microorganism inactivation employing almost monochromatic, low wavelength radiation has been studied using disinfection data obtained with Escherichia coli bacteria and germicidal UV lamps. This first contribution has been applied to experiments performed in a well-mixed reactor and describes the dose exploring two new concepts: (i) the use of the spatial distribution of the radiation absorption rates by the bacteria and (ii) the consideration that not necessarily the inactivation rate is of first order with respect to the radiation energy absorption rate. The proposed description agrees very well with the obtained experimental data for almost transparent water and for a medium having a concentrated culture with significant radiation absorption.